Analisis Efektivitas Penerimaan Pajak Daerah dan Kontribusinya Terhadap Pendapatan Asli Daerah Kota Padang (2020-2023) - Hidayatullah, Siti Rahmi; Nuraini, Miranda; Syawitri, Afriosa; Indra, Irma Suryani (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to analyze the effectiveness and contribution of hotel tax, restaurant tax, entertainment tax, street lighting tax, and BPHTB to the Original Regional Income of Padang City during the 2020-2023 period. This study uses a quantitative approach with descriptive statistical methods. The data used are the financial reports of the Padang City Government for the 2020-2023 period. The results of the study show that the average effectiveness of hotel tax and restaurant tax revenues is above 100% with the category